Apple cider vinegar in folk and modern medicine: a historical review and current scientific evidence. - Kiełb, Anna; Perkowska, Klaudia; Kaźmierczak, Anna; Izdebska, Wiktoria; Sornek, Patrycja; Borkowska, Agata; Pawlak, Igor; Mich, Anna; Ciesielski, Radosław; Stanek, Jakub (Quality in Sport, 2024)
Introduction and Aim of the Study: Apple cider vinegar (ACV) has been used for centuries in various cultural and medical contexts globally. This study seeks to explore ACV's traditional and contemporary applications, evaluating scientific evidence for its efficacy and safety. Material and Methods: This review synthesizes information from PubMed, Google Scholar, and other scientific sources. Key search terms included "apple cider vinegar," "apple cider vinegar medical use," "apple cider vinegar antimicrobial effect," "apple cider vinegar lipid profile," "apple cider vinegar glucose level," "apple cider vinegar preparation," and "apple cider vinegar historical use." Results: Research supports ACV's traditional role as a disinfectant, demonstrating effectiveness against a range of bacteria and fungi. Both animal and human studies suggest ACV may help lower cholesterol and triglyceride levels while boosting HDL cholesterol. Evidence indicates ACV can enhance insulin sensitivity and reduce blood glucose levels, offering benefits for type 2 diabetes management. ACV shows antioxidant properties, potential for lowering blood pressure, and use in certain skin diseases, though further research is needed to confirm these effects. Conclusions: The historical use of ACV in traditional medicine finds partial support in modern scientific research. Its antimicrobial, lipid-modulating, and glucose-regulating properties are documented, suggesting potential benefits for cardiovascular health, weight management, and metabolic regulation. Nonetheless, the evidence for its cosmetic applications and impact on muscle cramps remains less definitive. Additional research involving larger, diverse populations is necessary to fully validate ACV's benefits and establish safe usage guidelines.